2022
DOI: 10.3390/mi13040593
|View full text |Cite
|
Sign up to set email alerts
|

Digital Microfluidic Mixing via Reciprocating Motions of Droplets Driven by Contact Charge Electrophoresis

Abstract: Contact charge electrophoresis (CCEP) is an electrically controllable manipulation technique of conductive droplets and particles by charging and discharging when in contact with the electrode. Given its straightforward operation mechanism, low cost, and ease of system construction, it has gained traction as a versatile and potential strategy for the realistic establishment of lab-on-a-chip (LOC) in various engineering applications. We present a CCEP-based digital microfluidics (DMF) platform with two parallel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…The controlled transport of electrically charged liquid droplets has important applications in controlled drug delivery and in the separation of micro/macro molecules [73][74][75][76][77]. Charged liquid droplets suspended in an immiscible fluid can be manipulated employing EFs [78].…”
Section: Dropletsmentioning
confidence: 99%
See 2 more Smart Citations
“…The controlled transport of electrically charged liquid droplets has important applications in controlled drug delivery and in the separation of micro/macro molecules [73][74][75][76][77]. Charged liquid droplets suspended in an immiscible fluid can be manipulated employing EFs [78].…”
Section: Dropletsmentioning
confidence: 99%
“…Recent studies have used EPDD for merging aqueous droplets and minimizing direct liquidsolid contact. A recent study by Kim et al [74] reported the electrocoalescence and merging of droplets by employing a programmable digital microfluidics device. Their digital device consisted of two parallel electrode modules that enabled 3D programmable droplet handling.…”
Section: Electrophoretic Patterning Of Dropletsmentioning
confidence: 99%
See 1 more Smart Citation
“…Channel-based microfluidics suffer from clogging issues due to the narrow sizes of the channels [ 7 , 8 ]. Digital microfluidics, which relies on the movement of drops, is, alternatively, relatively more immune to this problem [ 9 , 10 , 11 , 12 ]. One of the exciting areas of application of digital microfluidics is in the creation of micro-reactors [ 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, they have gained widespread utility in microfluidic control, drug delivery, and biomedical research. [8][9][10] Furthermore, in contrast to bulk phases, charged microdroplets possess unique attributes such as the presence of an interface double layer, high electric fields, pH gradients, and rapid mixing and diffusion of surface molecules. [11][12][13][14] This micro-environment resembles a confined cell, promoting chemical reactions, including acceleration, selectivity control, and the facilitation of challenging reactions under conventional conditions.…”
mentioning
confidence: 99%